2018
DOI: 10.11591/ijece.v8i6.pp4584-4592
|View full text |Cite
|
Sign up to set email alerts
|

MetOp Satellites Data Processing for Air Pollution Monitoring in Morocco

Abstract: <p>This paper presents a data processing system based on an architecture comprised of multiple stacked layers of computational processes that transforms Raw Binary Pollution Data coming directly from Two EUMETSAT MetOp satellites to our servers, into ready to interpret and visualise continuous data stream in near real time using techniques varying from task automation, data preprocessing and data analysis to machine learning using feedforward artificial neural networks. The proposed system handles the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Air pollution in urban areas increases interest to researchers and political communities [11] due to its negative impact on human health and comfort. Many studies have demonstrated that breathing diseases may occur in peaks of air pollution [12].…”
Section: Air Pollution and Air Quality Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Air pollution in urban areas increases interest to researchers and political communities [11] due to its negative impact on human health and comfort. Many studies have demonstrated that breathing diseases may occur in peaks of air pollution [12].…”
Section: Air Pollution and Air Quality Platformsmentioning
confidence: 99%
“…Experiments showed that the structure achieves better performance than traditional process methods. Zaytar [11] presented a system to process the BUFR files coming directly from satellite sensors and transform them into a dataset ready for analysis and visualization. Boudriki Semlali [14] developed a Java-based application software to collect, process, and visualize environmental and pollution data acquired from the MDEO platform.…”
Section: Related Workmentioning
confidence: 99%
“…i) statistical-based approach, ii) logical approach, iii) outlier-detection approach, and iv) trajectory-based approach. The statistical-based approach is developed emphasizing time-series, prediction, trip detection, quantitative patterns, machine learning [39][40][41][42][43][44][45][46][47][48]. The existing logical-based approaches are reported to consider velocity constraints, reduction of travel distance, and human navigational system [49][50][51].…”
Section: Existing Research Trendsmentioning
confidence: 99%
“…The World Health Organization (WHO) first alerts the People's Republic of China and its other member states and then declares a public health emergency of international concern on January 30, 2020 [2]. The Covid-19 epidemic was declared a pandemic by the WHO on March 11, 2020, which calls for essential protective actions to prevent overcrowding in intensive care units and to strengthen preventive hygiene [3]. This global pandemic is causing a series of cancellations of sporting and cultural events around the world, the implementation by many countries of containment measures to curb the formation of new outbreaks of contagion and the closure of borders in many countries [4].…”
Section: Introductionmentioning
confidence: 99%